The Role of Matrix Metalloproteinases in the Epithelial-Mesenchymal Transition of Hepatocellular Carcinoma - Cristian Scheau; Ioana Anca Badarau; Raluca Costache; Constantin Caruntu; Gratiela Livia Mihai; Andreea Cristiana Didilescu; Carolina Constantin; Monica Neagu (Analytical Cellular Pathology)
The epithelial-mesenchymal transition (EMT) is a transformation process mandatory for the local and distant progression of many malignant tumors, including hepatocellular carcinoma (HCC). Matrix metalloproteinases (MMPs) play significant roles in cellular regeneration, programmed death, angiogenesis, and many other essential tissular functions, involved in the normal development and also in pathological processes, such as the EMT. This paper reviews the roles of MMPs in the EMT involved in HCC invasion, as well as the ancillary roles that MMP cross-activation and tissue inhibitors play in modulating this process. While gelatinases MMP-2 and MMP-9 are the MMPs commonly cited in the EMT of HCC, MMPs belonging to other classes have been proven to be involved in this process, favoring not only invasion and metastasis (MMP-1, MMP-3, MMP-7, MMP-10, MMP-11, MMP-13, MMP-14, MMP-16, MMP-26, and MMP-28) but also angiogenesis (MMP-8 and MMP-10). There is also data suggesting that other MMPs with a suspected or demonstrated role in the EMT of other cancers may also have some degree of involvement in HCC. The auto- and cross-activation of MMPs may complicate this issue, as pinpointing the extent of implication of each MMP may be extremely difficult. The homeostasis between MMPs and their tissue inhibitors is essential in preventing tumor progression, and the disturbance of this stability is another entailed factor in the EMT of HCC, which is addressed herein.